Treatment of radiation-induced acute intestinal injury with bone marrow-derived mesenchymal stem cells - ZHENG, KAI (Exp Ther Med, 2016)
The aim of the present study was to investigate the ability of bone marrow-derived mesenchymal stem cells (BMSCs) to repair radiation-induced acute intestinal injury, and to elucidate the underlying repair mechanism. Male Sprague-Dawley rats were subjected to whole abdominal irradiation using a single medical linear accelerator (12 Gy) and randomly assigned to two groups. Rats in the BMSC-treated group were injected with 1 ml BMSC suspension (2×10(6) cells/ml) via the tail vein, while the control group rats were injected with normal saline. BMSCs were identified by detecting the expression of CD29, CD90, CD34 and CD45 using flow cytometry. The expression of the cytokines stromal cell-derived factor 1 (SDF-1), prostaglandin E2 (PGE2) and interleukin (IL)-2 was detected using immunohistochemical techniques. Plasma citrulline concentrations were evaluated using an ELISA kit. Rat general conditions, including body weight, and changes in cellular morphology were also recorded. The results suggested that BMSCs exerted a protective effect on radiation-induced acute intestinal injury in rats. The histological damage was rapidly repaired in the BMSC-treated group. In addition, the BMSC-treated group showed significantly reduced radiation injury scores (P<0.01), mildly reduced body weight and plasma citrulline levels, significantly more rapid recovery (P<0.01), significantly reduced expression of the cytokines PGE2 and IL-2 (P<0.05) and significantly increased SDF-1 expression (P<0.01) compared with the control group. In summary, the present results indicate that BMSCs are able to effectively reduce inflammation and promote repair of the structure and function of intestinal tissues damaged by radiation exposure, suggesting that they may provide a promising therapeutic agent.